Policies and Patterns in US For-Profit Higher Education - Meza, Elizabeth; Zumeta, William (International Higher Education, 2014)
For-profit higher education in the USA grew to 10% market share of all higher education enrollments as of 2010 before falling back a bit under federal regulatory pressure. State policies toward the sector have remained largely unexamined, however. We take a first cut at documenting the policy postures individual states take toward for-profit institutions - on such dimensions as financial aid, information disclosure, program review requirements, etc. - and determine that states with more active policy saw larger FP enrollment growth from 2000-2010. The direction of causation is unclear, though.